2013
DOI: 10.1089/ars.2011.4421
|View full text |Cite
|
Sign up to set email alerts
|

Prx I Suppresses K-ras-Driven Lung Tumorigenesis by Opposing Redox-Sensitive ERK/Cyclin D1 Pathway

Abstract: These findings provide a better understanding of oxidative stress-mediated lung tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 54 publications
3
56
0
Order By: Relevance
“…In addition, Nrf2 also significantly increased in accordance with increased expression of Prx I. Furthermore, Nrf2 bound to the Prx I promoter region to regulate Prx I gene expression, as reported in lung cancer cells [11, 26]. Like Nrf2, FoxM1 also significantly increased in accordance with increased expression of Prx I in H-Ras G12V HCC cells.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, Nrf2 also significantly increased in accordance with increased expression of Prx I. Furthermore, Nrf2 bound to the Prx I promoter region to regulate Prx I gene expression, as reported in lung cancer cells [11, 26]. Like Nrf2, FoxM1 also significantly increased in accordance with increased expression of Prx I in H-Ras G12V HCC cells.…”
Section: Discussionsupporting
confidence: 58%
“…Our data confirmed the results of previous studies on cellular and animal NSCLC models regarding interrelationship of these two oncogenes. It was shown that KRAS knockdown in both A549 and NCI-H358 cells decreased the levels of cyclin D1 expression compared with control groups [31], while persistent exposure of mouse epithelial cells to nicotine stimulated RAS signaling, and subsequently increased cyclin D1 promoter activity and its protein expression [32]. Additionally, analysis of alterations in cell cycle regulatory genes in bitransgenic mouse model that inducibly expressed the human mutant KRAS allele showed no change in cyclin D1 RNA expression, while increased staining for cyclin D1 was detected [33].…”
Section: Discussionmentioning
confidence: 98%
“…Also, PTEN null mouse embryonic fibroblasts are resistant to ROS mediated induction of Prx1/Prx2 expression [81]. Prx1 may also be required for the ROS mediated activation of the K-Ras/ERK pathway that contributes to lung tumorigenesis [82]. Moreover, Prx1 along with Prx4 play essential roles in the regulation of c-Jun and AP-1 mediated promoter activity in lung cancer cells [83], and activation of Prx1 by histone deacetylase inhibitor FK228 result in induction of apoptosis in esophageal tumor cells [84].…”
Section: The Srx-prx Axis In Tumorigenesis and Cancer Progressionmentioning
confidence: 99%